Detection of Babesia caballi and Theileria equi in Blood from Equines from Four Indigenous Communities in Costa Rica - María Fernanda Posada-Guzmán; Gaby Dolz; Juan José Romero-Zúñiga; Ana Eugenia Jiménez-Rocha (Veterinary Medicine International)
A cross-sectional study was carried out in four indigenous communities of Costa Rica to detect presence and prevalence of Babesia caballi and Theileria equi and to investigate factors associated with presence of these hemoparasites. General condition of horses (n=285) was evaluated, and hematocrits and hemoglobin were determined from blood samples of 130 horses, which were also analyzed using blood smears, nested polymerase chain reaction (PCR), and immunosorbent assay (c-ELISA). The general condition of the horses (n=285) in terms of their body and coat was between regular and poor, and hematocrit and hemoglobin average values were low (19% and 10.65 g/dL, resp.). Erythrocyte inclusions were observed in 32 (24.6%) of the samples. Twenty-six samples (20.0%) gave positive results for B. caballi and 60 (46.2%) for T. equi; 10 horses (7.7%) showed mixed infection, when analyzed by PCR. Using c-ELISA, it was found that 90 (69.2%) horses had antibodies against B. caballi and 115 (88.5%) against T. equi, while 81 (62.3%) showed mixed reactions. There were no factors associated with the presence of B. caballi and T. equi. These results contrast with results previously obtained in equines in the Central Valley of Costa Rica.